Modelling and optimizing material flows in electrical energy distribution – first model - Cabrera Gonzales, Ernesto; Illés, Béla; Cservenák, Ákos (Advanced Logistic Systems - Theory and Practice, 2023)
The paper focuses on modelling and optimizing the distribution of material flows in a first version. Furthermore, the focus is on electrical energy flows, considering different energy sources and types of consumers. The most commonly used energy sources are nuclear, thermal, renewable and geothermal. The main categories of consumers include industry, residential, commercial and, increasingly, electric transportation. A first model is proposed which uses matrices for the various time constraints and uses graph theory to represent the flow of energy between sources and consumers. Variables and constraints are established to ensure that the flow remains within maximum capacities and meets minimum demands. In addition, a first version of mathematical model is proposed to minimize total energy supply costs.